Aggregation of Lactobacilli and Bifidobacteria with Escherichia coli O157 - Bujnáková, D; Vlková, E; Rada, V; Kmet, V (Folia microbiologica, 2004)
A total of 5 Bifidobacterium spp. isolated from pig and children' feces and 6 Lactobacillus spp. from chicken feces were examined for expression of aggregation, cell surface hydrophobicity (CSH) and adherence to intestinal mucin. Co-aggregation activity was seen in 3 strains of auto-aggregative bifidobacteria and 4 auto-aggregative strains of Lactobacillus spp. with 2 enterohemorrhagic E. coli (O157). CSH correlated with Lactobacillus auto-aggregating activity and adherence to mucin but the correlation between Bifidobacterium adherence to mucin and CSH was not confirmed.
Keywords: kur domácí; Hydrophobic and Hydrophilic Interactions; prasata; Feces; Swine; Mucins; hydrofobní a hydrofilní interakce; Chickens; Escherichia coli O157; Lactobacillus; Bacterial Adhesion; muciny; Animals; lidé; Humans; zvířata; Bifidobacterium; bakteriální adheze; feces